Nervilia kasiensis (Orchidaceae), a new record for the flora of Vietnam - Cong, Vu Kim; Vinh, Tran Thai; Bing, H’Yon Nie; Tham, Dang Thi; Hoi, Quach Van; Duy, Nong Van (Academia Journal of Biology, 2021)
Nervilia kasiensis is reported here as a new record for the flora of Vietnam. It is illustrated with detailed photographs made in the field. A key for the identification of all species of Nervilia genus known in Vietnam is presented.